Promoter polymorphism (T‐1486C) of TLR‐9 gene is associated with knee osteoarthritis in a Turkish population. Issue 11 (29th March 2017) - Balbaloglu, Ozlem; Sabah Ozcan, Seda; Korkmaz, Murat; Yılmaz, Neziha
ABSTRACT: In this study, we aimed to determine whether TLR‐9 T‐1486C SNP was associated with susceptibility to OA in the Turkish population. The study group comprised 272 patients with Grade 2‐3‐4 knee OA according to the Kellgren‐Lawrence scoring system and the control group was formed of 296 individuals with Grade 0–1. The TLR‐9 genotype were assessed by real‐time polymerase chain reaction. An analysis of TLR‐9 promoter −1486T/C polymorphism revealed that the −1486CC genotype appeared to have a higher risk for OA and −1486TT and −1486CT genotypes have a protective effect against the development of OA (crude OR = 0.473, 95% CI = 0.297–0.754, p = 0.002, adjusted OR = 0.531, 95% CI = 0.326–0.864, p = 0.011). This study indicate that there is a correlation of TLR‐9 T‐1486C gene polymorphism with advanced knee OA in a Turkish population. Changed in TLR expression due to different allelles may cause osteoarthrith development outcome cartilage degeneration. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2484–2489, 2017.